Geochemical Characteristics and Fluid Properties of the Qixia Formation Dolomites of the Middle Permian in the Shuangyushi Block, NW Sichuan Basin, China - Xu, Wenli; Zhou, Gang; Wan, Cixuan; Zhang, Lianjin; Tao, Jiali; Xu, Changhai; Yan, Xue (Frontiers in Earth Science, 2022)
The major and trace elements, REE (rare earth elements), carbon and oxygen isotopic compositions, strontium isotopes and fluid inclusions were analyzed for a petrology-based systematic study of the geochemical characteristics and fluid properties of the dolomites from the Middle Permian Qixia Formation in Shuangyushi block, northwestern Sichuan Basin. The analytical results of samples demonstrate that the Qixia Formation dolomites are mainly composed of medium, coarse, medium-coarse crystalline and anisocrystalline dolomites, with cloudy centers and clear rims. They generally exhibits dark purple luminescent in the centers and orange red luminescent in the rims. They are relatively highly ordered. The CaO and MgO contents show a negative correlation with each other. They are characterized by high Mg/Ca ratio, high Fe, Mn, Na contents and low Sr content. They have low total concentration of REE and similar REE distribution patterns to bioclastic limestone characterized by enrichment of light REE, depletion of heavy REE, and positive anomalies of Eu and Ce. They have consistent δ13C and δ18O values with the coeval seawater, and salinity index Z>120. Their diagenetic temperature is higher than normal temperature. Most of the 87Sr/86Sr values of the dolomites are higher than those of the coeval seawater, while some samples are very close to those of the coeval seawater. Their homogenization temperature of fluid inclusions exceeds 100℃, which is equivalent to the buried paleogeothermal temperature, and their salinity is 3-5 times that of normal seawater. Based on the regional geological setting and previous research achievements, the dolomitization fluids in the Qixia Formation are probably derived from seawater or marine fluids sealed in pores under shallow-burial reducing environment. The dolomites experienced late alternation by deep high-salinity hydrothermal fluids, and were formed earlier than the Middle-Late Triassic Period.